2013
DOI: 10.1016/j.ejca.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nicotine inhibits the therapeutic effects of gemcitabine on pancreatic cancer in vitro and in mouse xenografts

Abstract: Aim of Study Smoking is an established risk factor for pancreatic cancer and nicotine replacement therapy often accompanies chemotherapy. The current study hs tested the hypothesis that chronic exposure to low dose nicotine reduces the responsiveness of pancreatic cancer to the leading theraputic for this cancer, gemcitabine. Methods The effects of chronic nicotine (1 μm/L) on two pancreatic cancer cell lines in vitro and in a xenogaft model were assessed by immunoassays, Western blots and cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
2
28
0
2
Order By: Relevance
“…This phenomenon may be partly due to the increased phosph-Akt and/or phosph-Erk in mutant clones. As Baneriee et al [19] reported, the reduction in p-Erk contributed to the reduced sensitivity of pancreatic ductal adenocarcinoma (PDAC) to gemcitabine. Over-expressed p-Erk was also reported to enhance the drug resistance to 5-FU [20] and docetaxel [21].…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon may be partly due to the increased phosph-Akt and/or phosph-Erk in mutant clones. As Baneriee et al [19] reported, the reduction in p-Erk contributed to the reduced sensitivity of pancreatic ductal adenocarcinoma (PDAC) to gemcitabine. Over-expressed p-Erk was also reported to enhance the drug resistance to 5-FU [20] and docetaxel [21].…”
Section: Discussionmentioning
confidence: 97%
“…PDAC tumors developed in mice exposed to nicotine display more aggressive features, with increased number of circulating cancer cells and dissemination to the liver, compared with not-exposed mice. Moreover, these tumors are more resistant to gemcitabine chemotherapy (Banerjee, Al-Wadei, & Schuller, 2013). Obesity and abdominal fatness also increase PanIN and PDAC risks (RR: 2) (Aune et al, 2012;Rebours et al, 2015).…”
Section: Precancerous Lesions: Pancreatic Intraepithelial Neoplasia mentioning
confidence: 99%
“…Ortanca genel sağ kalım tedavi almayan kol için 1 ay (0,2-1,7) iken almış olan kolda 7 (4,7-9,3) ay idi (p<0,0001). Metastatik hastalar için ortanca PFS 23 hafta (19)(20)(21)(22)(23)(24)(25)(26)(27) idi. Gemsitabin tek başına verildiğinde(n=12) ortanca PFS 9 hafta (0, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]6) iken sisplatin tedaviye eklendiğinde(n=56) 25 (18,9) haftaya uzamıştı (p=0,001).…”
Section: Metastatik Hastalarunclassified